2014
DOI: 10.1159/000368217
|View full text |Cite
|
Sign up to set email alerts
|

The Serum Level of Brain Natriuretic Peptide Increases in Severe Subarachnoid Hemorrhage thereby Reflecting an Increase in Both Cardiac Preload and Afterload

Abstract: Background: The increase of serum brain natriuretic peptide (sBNP) is well known in patients with severe subarachnoid hemorrhage (SAH). However, the pathophysiology between the clinical severity of SAH and the sBNP secretion is still not clear. The aim of this study is thus to clarify the cardiovascular pathophysiological mechanisms of sBNP secretion in severe SAH patients. Methods: From the database of multicenter prospective study (SAH PiCCO study), sBNP level was compared among initial Hunt and Kosnik (H-K)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…14,25 Excessive catecholamine secretion, such as epinephrine and norepinephrine, occurs in the majority of aneurysmal SAH cases, causing sympathetic nervous system activation especially in severe cases, 12,19,20 resulting in the occurrence of systemic complications such as pulmonary cardiac lung edema, arrhythmia, or heart failure, 11,21,28 and reflect the primary brain injury itself. Yokobori et al 32 reported that serum BNP was significantly correlated with SAH grading and was a useful biomarker of systemic clinical impact, reflecting increased cardiac preload and afterload in severe aneurysmal SAH. Because of the breakdown of the blood-brain barrier by the ruptured aneurysm, increasing leukocyte trafficking has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…14,25 Excessive catecholamine secretion, such as epinephrine and norepinephrine, occurs in the majority of aneurysmal SAH cases, causing sympathetic nervous system activation especially in severe cases, 12,19,20 resulting in the occurrence of systemic complications such as pulmonary cardiac lung edema, arrhythmia, or heart failure, 11,21,28 and reflect the primary brain injury itself. Yokobori et al 32 reported that serum BNP was significantly correlated with SAH grading and was a useful biomarker of systemic clinical impact, reflecting increased cardiac preload and afterload in severe aneurysmal SAH. Because of the breakdown of the blood-brain barrier by the ruptured aneurysm, increasing leukocyte trafficking has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated its prognostic significance in patients with ischemic stroke, [22][23][24][25] traumatic brain injury, 26 intracranial hemorrhage, 27,28 and subarachnoid hemorrhage. 29,30 Emerging preclinical data suggest an adaptive role for BNP in recovery from acute brain injury. 31 Increased cerebral blood flow is seen with an increase in BNP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Aneurysmal SAH patients are a unique population of patients with a high risk of cardiac complications including stress cardiomyopathy and systolic dysfunction [23]. High-grade patients are also more likely to have abnormal preload and afterload [24]. Choosing a vasopressor with inotropic activity may have a particular importance in these patients.…”
Section: Discussionmentioning
confidence: 99%